A non-axisymmetric E × B shear inducing toroidally localized turbulence with an applied magnetic perturbation field in EAST. (13th November 2019) - Hu, G.H.; Chen, R.; Xu, G.S.; Guo, H.Y.; Sun, Y.W.; Liang, Y.F.; Xie, J.L.; Zhou, C.; Jin, X.L.; Gu, S.; Jia, M.N.; Wang, Y.F.; et al.
Abstract: The local E   ×   B shear has been demonstrated to be correlated with control of the 3D structure of turbulence in the edge transport barrier (pedestal) on EAST with edge-localized modes (ELMs) suppressed by externally applied 3D magnetic fields. The toroidal variations in turbulence intensity, spectrum width and eddy tilting are found to be correlated with the local E   ×   B shear, and may thus provide the potential mechanism for 3D-field-induced non-axisymmetric E   ×   B shear in regulation of the turbulence. These new findings may significantly advance the understanding of pedestal transport and structure with applied 3D fields for ELM control, which is critical for next-step fusion development.